FENOMENA AKUN ANONIM DI KALANGAN MAHASISWA DAN MAHASISWI BROADCASTING FIKOM UNIVERSITAS MERCU BUANA: SEBUAH STUDI KASUS - Wenny Pahlemy (Konvergensi, 2022)
The research entitled Anonymous Account Phenomenon among College Students and Students of the Faculty of Communication, Mercu Buana University is driven by technological developments in this case Instagram social media. This study aims to find and analyze the factors that encourage informants to have anonymous accounts on Instagram by interviewing a number of informants. This study uses the Social Construction Theory of Technology which explains the attraction relationship between technology and social groups of its users. This research uses case study method with collection method by interview, literature study, and documentation. The results showed that first, the use of anonymous accounts was strongly influenced by peers. Second, that technology in this case Instagram answers the informant's need for validation and for freedom of expression among informants. Third, having and being active on anonymous accounts has become a practice or culture among informants.